Rancangan Sistem Inventaris Barang IT Berbasis UI/UX pada Divisi IT Support PT. Dynantech International Menggunakan Metode Agile - Audry Safrina Zahra; Nenden Siti Fatonah (Lembaga Pengembangan Kinerja Dosen, 2026)
The advancement of information technology encourages companies to manage IT assets more effectively and in an integrated manner. PT. Dynatech International, as the Head Office responsible for handling the inventory of PT. Dynatech International and PT. Genecraft Labs, previously relied on manual record-keeping, which caused difficulties in asset tracking, loan management, and documentation of damage and maintenance history. This study aims to design a web-based IT inventory system using a UI/UX approach with the Agile (Scrum) method to improve the efficiency and accuracy of asset management. The research method employed is descriptive qualitative with a case study approach through observation, interviews, and literature review. The system development was carried out iteratively through product backlog, sprint planning, sprint development, sprint review, and sprint retrospective stages. The results show that the system is capable of managing the entire IT asset lifecycle, including inventory recording, loan requests, approval processes, damage reporting, and real-time ticket status monitoring. The intuitive UI/UX design enhances usability for both administrators and employees. The implementation of this system improves transparency, increases the efficiency of the IT Support Division’s performance, and supports faster and more accurate data-driven decision-making.